You Can’t Do It Right : Examining the Perceptual Challenges of 'Too Bossy' and 'Too Soft' in Female Leadership - Anzuck, Isabelle (2025)
This study explores how female leaders are perceived in the European context, where they continue to face a paradoxical double bind: assertiveness is often labelled as excessive, while empathy may be interpreted as weakness. Grounded in Social Role Theory and Role Congruity Theory, the research examines how gender stereotypes, emotional expectations, and culturally ingrained social norms shape the perception of leadership. The study does not advocate a specific solution, but it aims to contribute to a critical dialogue by illuminating the psychological and structural complexities underpinning gendered leadership evaluations. Employing an exploratory sequential qualitative design, the research combines a preliminary survey of 201 business students across EU countries with in-depth, semi-structured interviews with experienced leaders from diverse European industries. The survey provided generational insights into gendered leadership perceptions and informed the development of the interview guide. The interviews revealed that, despite increasing openness toward inclusive leadership models, deeply rooted implicit biases and gendered expectations persist. Female leaders reported heightened scrutiny, the need to balance confidence with likeability, and continued emotional double standards. The findings suggest that structural progress alone is insufficient without a concurrent cultural shift in how leadership is both defined and recognised. Rather than viewing gender equity as a matter of ticking boxes, the study highlights the need to challenge implicit mental models that privilege traditional, often masculine, leadership archetypes. Ultimately, the thesis calls for a redefinition of leadership ideals that transcends gendered assumptions, paving the way for a more psychologically inclusive and socially responsive leadership culture.